2019
DOI: 10.4491/eer.2018.347
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of fluorine in soil using calcium hydroxide and its potential human health risk

Abstract: This study assessed the stabilization of fluorine (F)-contaminated soil using calcium hydroxide (Ca(OH)2) and the consequent changes in human health risk. The bioavailable F decreased to 3.5%, (i.e., 57.9 ± 1.27 mg/kg in 6% Ca(OH)2-treated soil sample) from 43.0%, (i.e., 711 ± 23.4 mg/kg in control soil sample). This resulted from the conversion of water-soluble F to stable calcium fluoride, which was confirmed by XRD spectrometry. Soil ingestion, inhalation of fugitive dust from soil, and water ingestion were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Guo et al [187] have observed that -OH ions replace the exchangeable fluoride ions in an alkaline environment. Jeong et al [188] analyzed the fluoride stability in soil using calcium hydroxides and reported that the bioavailability of fluoride was reduced after calcium hydroxide treatment. The solubility of fluoride ions significantly depends upon soil pH (<4.9) and increases the organic matter [177], which possibly contaminates the groundwater for coarse-textured soil packing and shallow aquifers.…”
Section: Soilmentioning
confidence: 99%
“…Guo et al [187] have observed that -OH ions replace the exchangeable fluoride ions in an alkaline environment. Jeong et al [188] analyzed the fluoride stability in soil using calcium hydroxides and reported that the bioavailability of fluoride was reduced after calcium hydroxide treatment. The solubility of fluoride ions significantly depends upon soil pH (<4.9) and increases the organic matter [177], which possibly contaminates the groundwater for coarse-textured soil packing and shallow aquifers.…”
Section: Soilmentioning
confidence: 99%